2023
DOI: 10.3390/e25030395
|View full text |Cite
|
Sign up to set email alerts
|

Cryptanalysis of an Image Encryption Algorithm Based on Two-Dimensional Hyperchaotic Map

Abstract: This paper analyzes the security of an image encryption algorithm based on a two-dimensional hyperchaotic map. This encryption algorithm generated chaotic sequences through a combination of two one-dimensional chaotic maps and used them as the permutation and diffusion key. Then, the image was encrypted by using the structure of row–column permutation, forward-diffusion, and backward-diffusion. The proposer claimed that the above algorithm was secure. However, it was found through cryptanalysis that the algori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The recent study by Erkan et al 7 on the twodimensional Schaffer map's dynamic performance confirmed its hyperchaotic behaviour, surpassing traditional chaotic models. Jiang et al 8 utilized two-dimensional hyperchaotic mapping for key sequence generation, which is crucial in scrambling and encrypting image pixels. However, their approach highlighted limitations regarding computational complexity and scope of application.…”
Section: Introductionmentioning
confidence: 99%
“…The recent study by Erkan et al 7 on the twodimensional Schaffer map's dynamic performance confirmed its hyperchaotic behaviour, surpassing traditional chaotic models. Jiang et al 8 utilized two-dimensional hyperchaotic mapping for key sequence generation, which is crucial in scrambling and encrypting image pixels. However, their approach highlighted limitations regarding computational complexity and scope of application.…”
Section: Introductionmentioning
confidence: 99%
“…By assaulting the ciphertext, the security of encrypted data may be compromised using the cryptanalysis approaches [10]. For systems that employ encryption to successfully safeguard sensitive data, cryptanalysis must be avoided [11] [12]. In the encryption and decryption stages, contemporary block ciphers use permutation and substitution procedures [13].…”
Section: Introductionmentioning
confidence: 99%